Generation and Amplification of Third-Order Orbital Angular Momentum Modes in a Low-Loss All-Fiber System - Mengdi Zhang; Jianxiang Wen; Yan Wu; Ying Cao; Yanhua Luo; Xiaobei Zhang; Fufei Pang; Wei Chen; Tingyun Wang (IEEE Photonics Journal)
We theoretically and experimentally proposed the generation method of third-order orbital angular momentum (OAM) modes with reduced losses by cascading two adiabatic mode selective couplers (MSCs), in which the LP11 mode produced as an excitation mode was utilized to generate a higher-order mode (LP31). The minimum excess loss and insertion loss of cascaded MSCs were 3.7 dB and 5.3 dB, and had been greatly reduced compared to a single MSC. Then, the third-order OAM mode turned from LP31 mode was amplified in an all-fiber system, by which maximum mode gain after amplification can be achieved up to 23.2 dB. This generation and amplification system has promising applications in the long-distance mode division multiplexing technology.